Identities in the Sport Workplace: Development of an Instrument to Measure Sport Employee Identification. Issue 3 (2nd July 2020) - Oja, Brent D.; Bass, Jordan R.; Gordon, Brian S.
Abstract: Social identity theory (SIT) has proven to be a popular topic of discourse in academia. Scholars in the field of sport management have predominantly focused on team identification and how sport fans align with their favorite teams. However, recent developments have explored how sport employees identify with their sport organizations. To date, the maturation of theory involving sport employee identification (SEI) has only reached the conceptual stage. This study is intended to fill the void in the literature by creating a psychometric instrument to specifically measure SEI. The results indicate that SEI is a composite of two distinct but related factors, named sport affinity and collective enhancement. The instrument was subjected to and passed various reliability and validity tests. The appropriateness of using team identification variables to measure sport employees' social identities is also discussed. Lastly, theoretical and practical implications for the use of the instrument are provided.